2017
DOI: 10.15403/jgld.2014.1121.263.zul
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth-based Quadruple Therapy Following H. pylori Eradication Failures: a Multicenter Study in Clinical Practice

Abstract: Our study found that this bismuth-based quadruple therapy is highly effective as second-line and rescue therapy for H. pylori eradication in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Noteworthy, the success rate of such a therapy remained acceptably high until it was used as fourth‐line regimen, while it dropped to low values (<67%) only in those patients with more than 4 therapy failures. Such finding is in agreement with the results of a recent multicenter, Italian study where the success rate fell to 67% after 4 or more therapy failures . Therefore, such phenomenon deserves further investigation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Noteworthy, the success rate of such a therapy remained acceptably high until it was used as fourth‐line regimen, while it dropped to low values (<67%) only in those patients with more than 4 therapy failures. Such finding is in agreement with the results of a recent multicenter, Italian study where the success rate fell to 67% after 4 or more therapy failures . Therefore, such phenomenon deserves further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we administered the therapy for 10 days, and a longer 14‐day regimen should be tested. However, high eradication rates were achieved in using the same 10‐day regimen in three recent Italian studies, and in multicenter, European study …”
Section: Discussionmentioning
confidence: 96%
“…Although this study analyzed data of patients who underwent 7-day METbased second-line BQT, recent guidelines on H. pylori eradication therapy recommend 10-or 14-day, rather than 7-day, eradication for H. pylori. Several studies have showed results consistent with these guidelines [27,40].…”
Section: Discussionmentioning
confidence: 80%
“…Another finding that emerged from our study was that both therapeutic regimens were safe. The incidence of TEAEs of the bismuth plus omeprazole‐based quadruple regimen has already been well assessed in previous studies and varied from 26.7% to 67% of treated cases . In addition, the incidence of TEAEs was similar to those recorded with other eradicating therapies.…”
Section: Discussionmentioning
confidence: 57%